Reference Intervals for Plasma Biomarkers of Alzheimer's Disease. (20th December 2022) - Cooper, Jennifer G; Stukas, Sophie K; Ghodsi, Mohammad; Ahmed, Nyra; Holmes, Daniel; Wellington, Cheryl L
Abstract: Background: Several blood‐based biomarkers are emerging as potential screening, diagnostic, and prognostic tools for Alzheimer's disease (AD), including: the ratio of amyloid beta 42 over 40 (Aβ42/40), reflecting the pathology of amyloid plaques; phosphorylated tau‐181 (p‐tau‐181), reflecting the formation of neurofibrillary tangles; neurofilament light (NF‐L), reflecting axonal damage observed in neurodegeneration; and glial fibrillary acidic protein (GFAP), reflecting neuroinflammation through astrocyte activation. A critical step in the translation of these biomarkers from research to clinical implementation is establishment of reference intervals derived from an appropriate population. Methods: 900 plasma samples from male and female participants aged 3‐79 years old were analyzed for Aβ42/40, p‐tau‐181, NF‐L and GFAP to create reference intervals (RI). Samples are obtained from the Canadian Health Measures Survey (CHMS), a national study that collects demographics, health questionnaires, clinical data and biospecimens from participants. Analysis was preformed on the Quanterix Simoa HD‐X analyzer using the Neurology 4‐plex E and p‐tau‐181 assay. Discrete and continuous RIs were produced for each biomarker. Discrete RIs are produced according to the Clinical Laboratory Standards Institute guidelines (EP20‐A3c). Continuous RIs are created using quantile regression. Results: Participant samples were selected from the following age bins designated by the CHMS biobank: 3 to 5 years (N=56), 6 to 11 years (N=58), 12 to 19 years (N=58), 20 to 39 years (102), 40 to 59 years (N= 102), 60 to 79 years (N=140). After analysis, age partitions for discrete RI were created, resulting in two to five age‐bins per biomarker which reference intervals were generated for. Continuous RIs produced smooth centile curves across all ages, from which point estimates for any age can be calculated. Conclusions: Both discrete and continuous RIs for plasma Aβ42/40, p‐tau‐181, NF‐L and GFAP may help refine normative cut offs for each biomarker across the lifespan.